Pengaruh Likuditas dan Leverage Terhadap Financial Disress Pada Perusahaan Sektor Consumer non-cyclicals Yang Terdaftar pada Indeks Saham Syariah Indonesia di Bursa Efek Indonesia pada tahun 2018-2022 Dengan Profitabilitas Sebagai Variabel Intervening - Ardiansyah, Putra (ITB AAS INDONESIA Surakarta, 2024)
Financial distress is carried out to get an early warning of bankruptcy. The earlier warning indicators of bankruptcy appear, the greater the opportunity for management to prevent it. This research aims to: (1) identify and analyze the influence of liquidity (current ratio) and Leverage (debt to asset ratio) and profitability (return on assets) on Financial distress; and (2) identify and analyze the influence of liquidity (current ratio) and Leverage (debt to asset ratio) on Financial distress and profitability (return on assets) to mediate their respective influences. Research on non-cyclical consumer sector companies listed on the IDX in 2018-2022. The research population was 119 companies with a sample of 23 companies. The model for determining Financial distress used is the Zmjiweski model. Statistical analysis in this research was assisted by SmartPls Partial Least Square (PLS).Based on the results of the research and discussions that have been carried out, the research results can be concluded that liquidity has a significant and influential effect on Financial distress. Leverage has a significant and influential effect on Financial distress. Profitability has a significant influence on Financial distress and profitability is unable to mediate the influence of liquidity on Financial distress. Meanwhile, profitability is unable to mediate the effect of Leverage on Financial distress. Keywords liquidity, Leverage, Financial distress, profitability